Liebe/Inzest: Zur kulturellen Kodierung von Sexualität Dargestellt am Beispiel von J. M. R. Lenz’ Komödie «Der neue Menoza» (Studia theodisca, 2012)
In his comedy «Der neue Menoza», J. M. R. Lenz uses a love story between an exotic prince and a young German woman to simulate and debate a form of sexuality which the Bible disqualifies as incestuous. Inscribing a theological exegesis of incest as intertext in his framework, Lenz demonstrates the possibility of shifting this biblical taboo. Taking this perspective as the starting point of my investigation, I regard incest as a cultural construction. In the light of two contemporary discourses, the article points at the abrogation of the incest taboo by means of a re-writing of the biblical prohibition to be a sensitive issue in the cultural debate on sexuality.